(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Background: Adolescents in Denmark do not fulfil the recommendations for physical activity, and hopefully the FIT FIRST Teen programme could be part of the solution (Bangsbo et al., 2016; Krustrup et al., 2014; Larsen et al., 2018). Method: Ten participating schools completed three weekly 40-min FFT sessions with modified, motivating, involving, high-intensity sports-based activities. After the 10-wk. intervention period, one teacher from each school participated in an interview to determine the feasibility of the programme. Results: The teachers reported delivering all three weekly sessions with a maximum of two cancellations across the 10-week period due to other class obligations, and most teachers recommended to place the sessions as the last part of the school day, since some pupils showed a general disinterest in being physically active, while a more widely spread challenge was the pupils not feeling comfortable with working at high intensities and getting sweaty, out of breath, and red faced if they needed to go to other classes afterwards. Conclusion: FIT FIRST Teen shows promising feasibility and can be implemented in the Danish schools.